Street naming and innocent victims: a geography of anti-mafia memory in Italy (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
The article presents the results of the first census on the odonomastic memory of innocent victims of mafia violence in Italy. The intensity and location of the commemorative street-naming suggests the presence of an anti-mafia memory policy with spontaneous but concrete and effective characteristics. Odonomastic recurrences quantitatively account for the process of discursive heroification involving some victims.
Keywords: street-naming, memory, mafia, antimafia, territory